Teaching Mathematics during the COVID-19 Lockdown in a Context of Historical Disadvantage - Brantina Chirinda; Mdutshekelwa Ndlovu; Erica Spangenberg (MDPI AG, 2021)
The COVID-19 global pandemic widely affected education across the world and engendered unprecedented scenarios that required expeditious responses. In South Africa, the pandemic came on top of pre-existing inequalities in the education system. Using a qualitative research method of exploratory and descriptive nature, this study engaged a social justice framework to explore the teaching and learning of mathematics during the COVID-19 lockdown in a context of historical disadvantage. A sample of twenty-three Grade 12 mathematics teachers at various public secondary schools in Gauteng, South Africa was used in the study. The teachers were selected through purposive sampling. A Google-generated open-ended questionnaire and follow-up telephonic interviews were used to collect data. Data were analysed thematically in five steps. The findings revealed that the WhatsApp platform is a valuable tool that can support the teaching and learning of mathematics beyond the classroom in the contexts of historical disadvantage. The findings also provided insights into how mathematics teachers became learners themselves during emergency remote teaching (ERT) as they had to adapt to digital teaching, find solutions to unfamiliar problems and acquire knowledge from a larger mathematics education community around the globe. The article discusses these findings and teachers' challenges of transitioning from traditional face-to-face classrooms to ERT and how they were addressed. At the time of publishing the article, most learners in South Africa had started going to school on a rotational basis. Nonetheless, the study reported in this article is of importance as ERT in the context of historical disadvantage has foregrounded issues of inequality in the South African education system that must be dealt with urgently.